2017
DOI: 10.1186/s12870-017-1028-0
|View full text |Cite
|
Sign up to set email alerts
|

A relative quantitative Methylation-Sensitive Amplified Polymorphism (MSAP) method for the analysis of abiotic stress

Abstract: BackgroundWe present a new methylation-sensitive amplified polymorphism (MSAP) approach for the evaluation of relative quantitative characteristics such as demethylation, de novo methylation, and preservation of methylation status of CCGG sequences, which are recognized by the isoschizomers HpaII and MspI. We applied the technique to analyze aluminum (Al)-tolerant and non-tolerant control and Al-stressed inbred triticale lines. The approach is based on detailed analysis of events affecting HpaII and MspI restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 52 publications
(104 reference statements)
1
47
0
Order By: Relevance
“…Methylation-sensitive amplified polymorphism (MSAP) (Baranek et al 2016) uses HpaII and MspI endonuclease to study methylation changes within DNA sequences at the restriction sites. This approach was recently extended, enabling quantification of only the site DNA methylation alterations (Bednarek et al 2017). Methylation amplified fragment length polymorphism (metAFLP) enables quantitative analysis of both sequence and DNA methylation changes affecting Acc65I-KpnI restriction sites (Bednarek et al 2007;Chwedorzewska and Bednarek 2012;Machczyńska et al 2014b;Wódkiewicz et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Methylation-sensitive amplified polymorphism (MSAP) (Baranek et al 2016) uses HpaII and MspI endonuclease to study methylation changes within DNA sequences at the restriction sites. This approach was recently extended, enabling quantification of only the site DNA methylation alterations (Bednarek et al 2017). Methylation amplified fragment length polymorphism (metAFLP) enables quantitative analysis of both sequence and DNA methylation changes affecting Acc65I-KpnI restriction sites (Bednarek et al 2007;Chwedorzewska and Bednarek 2012;Machczyńska et al 2014b;Wódkiewicz et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Under drought treatment, a decrease of DNA methylation was observed in leaf tissues of two faba bean genotypes (Abid et al, 2017). Moreover, Bednarek et al (2017) observed an elevated demethylation in both non-tolerant and tolerant plants, with de novo methylation occurring less frequently than demethylation under Aluminum stress in triticale lines.…”
Section: Introductionmentioning
confidence: 88%
“…The MSAP profiles showing reproducible results between replicates were transformed into a binary matrix, with 1 as a presence of band and 0 the absence of band from either EcoRI/MspI or EcoRI/HpaII digestion and analyzed according to the protocol developed by Bednarek et al (2017). In general, these fragments could be divided into four types representing four types of DNA methylation status of the restriction sites (5′-CCGG-3′):…”
Section: Data Scoring and Analysis Of Msap Profilesmentioning
confidence: 99%
See 2 more Smart Citations